Fuzzy Logic Controlled Electromagnetic Actuated CVT system for passenger car - Rahman, Mohammed Ataur; Sazzad, Sharif (2013)
This paper encompasses development of a fuzzy logic controlled electromagnetic actuator (EMA) for better CVT operation of light automobile. The main objective of this study is to significantly reduce the delaying accelerating time of the vehicle and improve the transmission loss. EMA-CVT comprises of two sets of solenoids with a common plunger attached with primary and secondary pulley sheave. It will ensure the back and forth movement of plunger likewise sheave by exercising controlled electromagnetic attraction and repulsion force. Since the system is fully nonlinear in behaviour a concept of intelligent control system is introduce here. A Fuzzy Logic Controller (FLC) is developed to control the EMA nonlinear behaviour precisely based on the feedback. The fast response of the solenoids of the EMA was activated by varying the power supply of the alternator with the Fuzzy-Proportional-Derivative-Integrator (FPID) to maintain the non-linearity of the CVT in response of the vehicle traction torque demand accordingly. It develops electromagnetic forces 108 N for current 1.21 amp and 301 N for current 3.37 amp which are good enough to overcome the clamping force for the ¼ scale car the maximum 278 N. It is observed that travelling time of the plunger is in the range of 1.8– 3.1sec which could be considered as the acceleration time for the car.